Factors Affecting the Gender Mainstreaming in Nigeria's Government Sector - Makuachukwu, Ifeoma (International Journal of Gender Studies, 2023)
Purpose: The purpose of this study was to determine the influence of traditional practices, gender roles, religious practices and community perception on women in gender mainstreaming process in recruitment in Nigeria Methodology: The study adopted a desktop methodology Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low-cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Results: The results revealed that there exist conceptual and contextual gaps relating to the study on factors affecting the gender mainstreaming in Nigeria's government sector. Preliminary empirical review reveals that gender roles have a positive and significant influence on gender mainstreaming process in recruitment in Nigeria. Unique Contribution to Theory, Practice and Policy: Social constructionism theory and feminist theory may be used to categorize the key work design factors which may relate to gender mainstreaming factors that are important to this study. The results of this research will form the basis for further research to explain how culture, gender roles and community perception on women influence the gender mainstreaming process in recruitment.